Prawo do zawierania małżeństwa a wizja seksualności. Interpretacja etyczna - Grzybek, Grzegorz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Taking into account the variety of potential visions of sexuality, modern ethical standards, the dissimilarity of vital women and man ethos, and the transformation of modern morality, in spite of a distaste for the religious environment, the right to marriage should be connected with the right the dissolution of a marriage. The postulated equality means equality of this law for both woman and man, which was historically connected with different entitlements.
The right to get married versus the vision of sexuality: an ethical interpretation
Keywords: divorce; human rights; marriage; visions of sexuality